Separation of Oil, Grease and TSS in Chicken Intestine Chips Factory Wastewater Using a Laboratory-Scale Grease Trap Reactor - Deslyano Miyola Pratama; Evy Hendriarianti; Candra Dwiratna Wulandari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The chicken intestine chips factory UD Ratna in Mojosari, Mojokerto generates wastewater and has been operating a wastewater treatment plant (WWTP) using sedimentation and aeration processes powered by solar panels. However, the performance of the WWTP, which was constructed in 2023, has not yet met the effluent quality standards. The initial sedimentation process is often disrupted by floating oil and grease, which obstruct the flow and cause agglomeration of solid and suspended particles, making them difficult to settle.. This study is a laboratory-scale experimental research designed to evaluate the effectiveness of a laboratory-scale grease trap reactor in reducing oil and grease as well as total suspended solids (TSS) concentrations at flow velocity variations of 2 m/h, 4 m/h, and 6 m/h. The research stages began with sample collection followed by the operation of the grease trap reactor conducted at the Chicken Intestine Chips Factory UD Ratna. The results showed that the grease trap reactor was able to remove oil and grease and TSS concentrations. The highest removal of oil grease and TSS was obtained at a flow velocity of 2 m/h, with effluent concentrations of 10 mg/L and 323.33 mg/L, and removal efficiencies of 88.68% and 71.47%, respectively. At a flow velocity of 2 m/h, the oil and grease concentration met the wastewater quality standard, while the TSS concentration remained above the permitted standard according to Peraturan Menteri Lingkungan Hidup Republik Indonesia Nomor 5 Tahun 2014 tentang Quality standards Air Limbah.